Increased cancer incidence in children after cardiac catheterization within the first 8 years of life, a single center experience between 1999 and 2013. (3rd October 2022) - Scholtissek, H; Sheho, N; Spix, C; Kretschmer, A; Hager, A; Ewert, P; Meierhofer, C; Stern, H
Abstract: Background: Children with congenital heart disease are exposed to ionising radiation early in their lives when tissue sensitivity for radiation is highest. This might provoke DNA fractures and cancer development. Our first study with an observation period from 1980–1998 showed a 4.4-fold increased cancer risk for children who had at least one cardiac catheterization in the first year of life. Objectives: This study aimed to reassess the risk of cancer for children who underwent at least one cardiac catheterization between 1999 and 2013 with a follow-up of seven years. Methods: This retrospective, single-center study included 2765 children who underwent at least one cardiac catheterization before eight years of age between January 1999 and December 2013. 1688 received their first cardiac catheterization in the first year of life, 1074 between first and eighth year of life. Catheterization and patient data were obtained from our database, and cancer diagnoses up to age 15 were matched with German Childhood Cancer Registry. For each tumor patient and for each of the 60 randomly selected control patients cumulative effective radiation doses were calculated. Results: 37667.16 person-years were evaluated. A total of ten patients developed a malignant tumor, while 5.82 were expected (SIR 1.72; CI 0.82–3.16; p=0.0722). Eight of these ten tumors developed in patients who received their first cardiac catheterization in the first year of life, while 3.99 were expected (SIR 2.0; CI 0.71–3.62; p=0.1095). The cancer group performed an average of 3.7 cardiac catheterizations per patient, with a mean cumulative effective dose of 24, 79mSv. In the control group consisting of 60 patients, 2.1 cardiac catheterizations were performed per patient with an average cumulative effective dose of 21.04mSv. Three of the ten tumor patients have chromosomal abnormalities. The cancers observed are two leukemia, two lymphoma, two CNS tumors, one osteosarcoma, two nephroblastoma and one hepatoblastoma. Conclusion: There is still an increased risk of cancer development for children with congenital heart disease exposed to ionizing radiation early in life. However, due to technical development and increased sensitivity to this fact, we observed a decrease in cancer disease compared to our previous study with catherization between 1980 and 1998. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Stiftung Kinderherz